1999
DOI: 10.1177/1066480799074004
|View full text |Cite
|
Sign up to set email alerts
|

The Family Debriefing Model: An Adapted Critical Incident Stress Debriefing for Parents and Older Sibling Suicide Survivors

Abstract: The Family Debriefing Model is described. The Family Debriefing Model combines solution-focused interventions with an adaptedCritical Incident Stress Debriefing model and was specifically designed to facilitate treatment with parents and adult-and adolescent-siblings who survive a family member's suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Turning to studies of suicide specific intervention programs, a search was conducted of the PsychLit and the Suicide Information and Education databases for studies related to suicide bereavement and intervention/treatment. While numerous positive descriptions of groups or programs for survivors exist (Apel & Wrobleski, 1987; Freeman, 1991; Juhnke & Shoffner, 1999), only a handful of empirical studies have been conducted to assess the effectiveness of these programs. Given the dearth of methodologically rigorous research, we have included in this review any study that involved some type of objective evaluation of the effectiveness of the intervention, regardless of the utilization of control groups or random assignment.…”
Section: Suicide Specific Interventionsmentioning
confidence: 99%
“…Turning to studies of suicide specific intervention programs, a search was conducted of the PsychLit and the Suicide Information and Education databases for studies related to suicide bereavement and intervention/treatment. While numerous positive descriptions of groups or programs for survivors exist (Apel & Wrobleski, 1987; Freeman, 1991; Juhnke & Shoffner, 1999), only a handful of empirical studies have been conducted to assess the effectiveness of these programs. Given the dearth of methodologically rigorous research, we have included in this review any study that involved some type of objective evaluation of the effectiveness of the intervention, regardless of the utilization of control groups or random assignment.…”
Section: Suicide Specific Interventionsmentioning
confidence: 99%
“…The current solution‐focused applications also speak to recent research that has found that families who have lost a loved one to suicide have significant resiliency (Clark & Goldney, 1995; Davis & Nolen‐Hoeksema, 2001; Kaslow & Aronson, 2004; Murphy et al., 2003). In contrast to prevailing treatment approaches that are largely cognitive‐behavioral and psychoeducational (e.g., Dunne & Dunne‐Maxim, 2004; Forde & Devaney, 2006; Juhnke & Shoffner, 1999; Kubany, 1998; Maples et al., 2005; Roberts et al., 1998), solution‐focused therapy highlights families’ existing or potential resources and emphasizes the resiliency of families coping with suicide.…”
Section: Discussionmentioning
confidence: 99%
“…(1998). Juhnke and Shoffner (1999) have described a critical incident stress debriefing model for families that incorporates solution‐focused techniques. Each of these approaches is similar insofar as they are designed in a cognitive‐behavioral, structured, and/or educational format.…”
Section: Suicide and Familiesmentioning
confidence: 99%
See 2 more Smart Citations